Mechanism of Immunity against Campylobacter Jejuni in Mice - Ewuola, Kola Sambakeyu (2015)
The roles of B-lymphocytes, T-lymphocytes and macrophages in the mechanism of immunity against Campylobacter jejuni in mice were investigated. This was done in an attempt to proffer solution to the problem of diarrhea through the enhancement of the immune mechanism involved in the protection against this agent.